Space, Human and Sacred in Candomblé - Ibiapina, Felipe; Leitão , Lúcia (Risco - Journal of Architecture and Urbanism, 2021)
The essay seeks to discuss the relationship between the architectural space, man and the sacred in Candomblé, in order to understand the role assumed by architecture in this triad. The pape is a preliminar thesis result, that is in course, and before the field research. The basis adopted was the teoric mark, using as a epistemological perspective the dialogue between the western philosophy throw Heidegger and yoruba philosophy, organized by Muniz Sodré. The essay intents contribute with afro-brazilian studies into Arquitecture, legitimating the candomblé’s temple as a architecture object of study, opening this field for alterity, further the western racionalism.